Application of Ecofriendly Geopolymer Binder to Enhance the Strength and Swelling Properties of Expansive Soils - Opu Chandra Debanath; Md. Aftabur Rahman; Sultan Mohammad Farook; Mohammed Russedul Islam (Advances in Civil Engineering)
The expansive soil swells significantly in the presence of moisture, which often leads to the failure of superstructures. Conventional stabilization techniques are applied in many instances, although environmental issues are of significant concern for such stabilization. Keeping this in mind, an attempt is made to apply a new approach for stabilizing different types of expansive soils, treated with a nonconventional binder geopolymer that utilizes fly ash as the main ingredient. A series of laboratory experiments are run to determine the engineering properties of treated soils with varying percentages of geopolymer from 0% to 30%. The experimental investigation involved tests such as unconfined compressive strength, compaction, Atterberg limits, and swelling pressure. Significant strength development occurs with increasing percentages of geopolymer, and their swelling pressures decrease considerably. Additionally, a series of California Bearing Ratio (CBR) tests were undertaken to assess the suitability for road construction. The optimum dosage of the stabilizing agent is found to be 20%, as justified by studies in the literature. Furthermore, scanning electronic microscope (SEM) images of the treated samples revealed microstructural changes in the soil matrix, which strongly correlate with the improvement of strength and swelling behavior. Hence, based on our experimental results, 20% geopolymer content is sufficient for enhancing the engineering properties of expansive soils, and the treated soils can directly be used as subgrade or sub-base material.